Exploring cation disorder in mixed‐metal pyrochlore ceramics using 17O NMR spectroscopy and first‐principles calculations. (15th February 2021) - Fernandes, Arantxa; Moran, Robert F.; McKay, David; Griffiths, Ben L.; Herlihy, Anna; Whittle, Karl R.; Dawson, Daniel M.; Ashbrook, Sharon E.
Abstract: Characterising the local structures (e.g., the cation distribution) of mixed‐metal ceramics by NMR spectroscopy is often challenging owing to the unfavourable properties (low γ, large quadrupole moment and/or low abundance) of many metal nuclei. 17 O is an attractive option owing to the prevalence of oxygen within ceramics. The moderate γ and small quadrupole moment of 17 O mean that the greatest barrier to accessing the information available from this nucleus is isotopic enrichment. We explore the challenges of ensuring uniform isotopic enrichment with 17 O2 (g) for the pyrochlore solid solutions, Y2 Sn x Ti2– x O7, La2 Sn x Zr2– x O7 and La2 Sn x Hf2– x O7, demonstrating that high enrichment temperatures (900 °C for 12 hr) are required. In addition, for sites with very high symmetry (such as the tetrahedral OY4 and OLa4 sites with CQ ≈ 0 present here), we demonstrate that quantitative 17 O NMR spectra require correction for the differing contributions from the centreband of the satellite transitions, which can be as high as a factor of 3.89. It is common to use first‐principles calculations to aid in interpreting NMR spectra of disordered solids. Here, we use an ensemble modelling approach to ensure that all possible cation arrangements are modelled in the minimum possible number of calculations. By combining uniform isotopic enrichment, quantitative NMR spectroscopy and a comprehensive computational approach, we are able to show that the cation distribution in Y2 Sn x Ti2– x O7 is essentially random, whereas in La2 Sn x Zr2– x O7 and La2 Sn x Hf2– x O7, OLa2SnZr and OLa2SnHf sites are slightly energetically disfavoured, leading to a weak preference for clustering of like cations. Abstract : We combine uniform 17 O isotopic enrichment with quantitative 17 O NMR spectroscopy and comprehensive computational modelling to investigate cation disorder in the pyrochlore solid solutions, Y2 Sn x Ti2– x O7, La2 Sn x Zr2– x O7 and La2 Sn x Hf2– x O7 . We demonstrate that the cation distribution in Y2 Sn x Ti2– x O7 is essentially random, whereas in La2 Sn x Zr2– x O7 and La2 Sn x Hf2– x O7, the more 'mixed' OLa2SnZr and OLa2SnHf sites are slightly energetically disfavoured, leading to some deviation from a totally random cation distribution.